Pengaruh pengembangan multimedia edukasi dalam pemberdayaan keluarga memberi dukungan pengobatan penderita tuberkulosis paru - Tumiur Sormin; Anita Puri (Holistik Jurnal Kesehatan, 2022)
Background: The  preliminary study in Health Office (Dinkes) of South Lampung regarding the coverage of the Tuberculosis program  in 2017 and  2018 results were only 51% and 42.41%. While the target of treatment should be 100%. Pre-survey for patients with pulmonary tuberculosis  in the working area of the Natar Puskesmas families are 5 people (50%)  of  10  tuberculosis  sufferers  who  do  not  comply  with  their  treatment, said that there are no routine  treatment, 8  people  (80%) of  the family have not given serious support to family members who have pulmonary   tuberculosis  to   adhere   for   treatment  and have never received empowerment training from the health side. Purpose: To determine the effect of Multimedia Educational Development in Empowering Families to Support Treatment of Pulmonary Tuberculosis Patients.Method: Participant were divided into 6 groups, 10 people per group and every week it was divided into two groups. Each group gets three learning sessions. In the first session, participant were asked to listen to pulmonary TB material which was shown through educational videos for 2 x 25 minutes, interspersed with discussions and questions and answers. The material includes understanding, causes, signs and symptoms, complications, prevention, and treatment. In the second session, participant were asked to listen to an educational video about pulmonary TB prevention practices for 25 minutes and then asked participant to practice it for 25 minutes. In the third session, participant were asked to show an educational video about the practice of supporting the treatment of pulmonary TB patients for 25 minutes, then asked participant to practice it for 25 minutes. At the end of the presentation of the material, the participant were distributed booklets containing material for pulmonary TB and how to support the treatment of pulmonary TB patientsResults: Sampling of 60 people from 70 families of pulmonary TB patients in Kecamatan Natar Lampung Selatan used educational multimedia. The level of confidence with p-value < a (0.05).Conclusion: P value was obtained 0.000, so that there was a significant difference between the ability of participant to provide emotional support, appreciation, instrumental, information, treatment networks, healing motivation, directing behavior to recover, maintaining healing behavior and knowledge about pulmonary TB treatment in pulmonary TB patients. first and second. Overall support, the difference between the first and second measures of ability to provide treatment support was 0.217 with an SD of 0.613. The results of the statistical test obtained a P-value of 0.008, so that there was a significant difference between the participant ' ability to provide treatment support for patients with pulmonary TB in the first and second measurements.Keywords: Educational Multimedia; Family Empowerment; Pulmonary Tuberculosis TreatmentPendahuluan: Hasil studi pendahuluan ke Dinkes Lamsel, tentang cakupan program TB tahun 2017dan 2018 hanya 51% dan 42,41%. Sedangkan target pengobatan seharusnya 100% . Pre survey kepada keluarga penderita TB paru di wilayah kerja Puskesmas Natar 5 orang (50%) dari 10 penderita TB tidak patuh pengobatannya, mengatakan tidak rutin berobat, 8 orang (80%) dari keluarga belum memberi dukungan serius pada anggota keluarganya TB paru untuk patuh pada pengobatannya dan belum pernah mendapat  iatihan  pemberdayaan   dari  pihak  kesehatan.Tujuan: Untuk mengetahui pengaruh Pengembangan Multimedia Edukasi Dalam Pemberdayaan Keluarga Memberi Dukungan Pengobatan Penderita Tuberkulosis Paru.Metode: Partisipan dibagi dalam 6 kelompok, 10 orang per-kelompok dan setiap minggu dilakukan kepada dua kelompok. Setiap kelompok mendapatkan tiga sesi pembelajaran. Di sesi pertama reponden diminta untuk menyimak materi TB paru yang ditayangkan melalui video edukasi selama 2 x 25 menit diselingi diskusi dan tanya jawab. Materi mencakup pengertian, penyebab, tanda dan gejala, komplikasi, pencegahan serta pengobatan. Di sesi kedua partisipan diminta menyimak tayangan video edukasi tentang praktik pencegahan TB paru selama 25 menit kemudian meminta partisipan mempraktikkannya selama 25 menit.  Di sesi ketiga partisipan diminta menyimak tayangan video edukasi tentang praktik mendukung pengobatan pasien TB paru selama 25 menit, kemudian meminta partisipan mempraktikkanya selama 25 menit. Di akhir pemberian materi, kepada partisipan dibagikan booklet berisi materi TB paru dan cara mendukung pengobatan pasien TB parukapanHasil: Pengambilan sempel sebanyak 60 orang dari 70 keluarga penderita TB paru di Kecamatan Natar Lampung Selatan menggunakan multimedia edukasi Tingkat kepercayaan dengan p-value < a (0,05).Simpulan: Didapatkan P-value 0,000, sehingga disimpulkan ada perbedaan yang signifikan antara kemampuan partisipan memberikan dukungan emosional, penghargaan, instrumental, informasi, jaringan pengobatan, motivasi sembuh, mengarahkan perilaku sembuh, mempertahankan perilaku sembuh dan memberi pengetahuan tentang TB paru pengobatan pada penderita TB paru pengukuran pertama dan kedua. Secara analisis keseluruhan dukungan, perbedaan pengukuran pertama dan kedua kemampuan memberi dukungan pengobatan adalah 0,217 dengan SD 0,613. Hasil uji statistik diperoleh P-value 0,008, sehingga disimpulkan ada perbedaan yang signifikan antara kemampuan partisipan memberikan dukungan pengobatan pada penderita TB paru pengukuran pertama dan kedua.